2009
DOI: 10.1016/j.ssresearch.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant generation, selective acculturation, and alcohol use among Latina/o adolescents

Abstract: Do alcohol use and binge drinking among Latina/o adolescents increase in the second and third generation? This study explores generational differences in alcohol use behaviors for three Latina/o ethnic groups. Using data from the National Longitudinal Study of Adolescent Health on 1504 Latina/ o adolescents in secondary school, we found that the factors associated with alcohol use behaviors differed across the Latina/o groups. For Mexican and Cuban adolescents, but not Puerto Ricans, immigrant generation was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 53 publications
1
58
0
Order By: Relevance
“…Nativity (defined in this study as country of birth) plays a central role in shaping health outcomes, including substance use (Eitle, Wahl & Aranda 2009;Ojeda, Patterson & Strathdee 2008;Turner, Lloyd & Taylor 2006;Wahl & Eitle 2010), general health status (Cho, Frisbie & Rogers 2004;Uretsky & Mathiesen 2007), and mental health (Takeuchi et al 2007). Prior research about the role of nativity on substance use has indicated some concordance with the immigrant health advantage concept.…”
Section: Nativity and Substance Usementioning
confidence: 90%
“…Nativity (defined in this study as country of birth) plays a central role in shaping health outcomes, including substance use (Eitle, Wahl & Aranda 2009;Ojeda, Patterson & Strathdee 2008;Turner, Lloyd & Taylor 2006;Wahl & Eitle 2010), general health status (Cho, Frisbie & Rogers 2004;Uretsky & Mathiesen 2007), and mental health (Takeuchi et al 2007). Prior research about the role of nativity on substance use has indicated some concordance with the immigrant health advantage concept.…”
Section: Nativity and Substance Usementioning
confidence: 90%
“…Most studies assessed the role of cultural factors such as acculturation or linguistic factors and individual or psychological stressors associated with the migration process (Almeida et al, 2012;Castañeda et al, 2015;Chen et al, 2000;Cheung, 2014;Eitle et al, 2009;Gil et al, 2000;Gordon-Larsen et al, 2003;Lara et al, 2005;Rostila, 2010;Warner et al, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 2010). Yet, as argued elsewhere, research on migration and health may have over-emphasised the role of cultural factors (including, among others, values and beliefs) and it may instead need a better understanding of the role of structural social determinants of health (Castañeda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, to improve effectiveness of the prospective alcohol-related strategies, it is critical to discover and understand the causes and risk factors for drinking in adolescence [4,17,24]. A number of previous studies showed that the leading motives for drinking among adolescents often involve social aspects, with alcohol as a lifestyle element that defines one's social identity [4,9,[42][43][44][45][46]. Teens usually consume alcohol at celebrations or parties where drinking is encouraged, with the intention to avoid social rejection, facilitate interactions with others, and to have fun [1,2,15,17,42,45,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%